THE EFFECT OF AI AS AN ONLINE TUTOR AND DIGITAL LITERACY ON LEARNING COMPREHENSION A SEM APPROACH - Guntur Gunawan; Yuyun Yumiarty (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
This study aims to analyze the effect of AI as an online tutor and digital literacy on students’ learning comprehension. The research employed a quantitative approach with an explanatory survey design involving 100 students from the PGMI Study Program at IAIN Curup. The research instrument was a Likert-scale questionnaire measuring three main constructs: AI as an online tutor, digital literacy, and learning comprehension. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test validity, reliability, and the structural relationships among variables. The results indicate that AI as an online tutor has a positive and significant effect on learning comprehension (? = 0.425; p < 0.000). Digital literacy also has a positive and significant effect on learning comprehension (? = 0.476; p < 0.000). The R-square value of 0.699 shows that 69.9% of the variance in learning comprehension can be explained by these two independent variables. Overall, this study confirms that the integration of AI-based technology, supported by students’ digital literacy skills, can enhance the quality of learning comprehension in higher education.